CDK4 and miR-15a comprise an abnormal automodulatory feedback loop stimulating the pathogenesis and inducing chemotherapy resistance in nasopharyngeal carcinoma. Issue 1 (December 2016) - Liu, Zhen; Cheng, Chao; Luo, Xiaojun; Xia, Qiong; Zhang, Yejie; Long, Xiaobing; Jiang, Qingping; Fang, Weiyi
Abstract Background In previous investigation, we reported that stably knocking down cyclin-dependent kinase 4(CDK4) induced expression of let-7c, which further suppressed cell cycle transition and cell growth by modulating cell cycle signaling in nasopharyngeal carcinoma (NPC). In this study, we further explored the molecular function and mechanism of CDK4 modulating miRNAs to stimulate cell cycle transition, cell growth, and Cisplatin (DDP) -resistance on in NPC. Methods We identified changes in miRNAs by miRNA array and real-time PCR and the effect on DDP after knocking down CDK4 in NPC cells. Further, we investigated the molecular mechanisms by which CDK4 modulated miR-15a in NPC. Moreover, we also explored the role of miR-15a and the effect on DDP in NPC. Finally, we analyzed the correlation of miR-15a and CDK4 expression in NPC tissues. Results In addition to let-7 family members, we observed that upregulated expression of miR-15a was significantly induced in CDK4-suppressed NPC cells. Further, we found that knocking down CDK4 suppressed c-Myc expression, and the latter directly suppressed the expression of miR-15a in NPC. Furthermore, miR-15a as a tumor suppressor antagonized CDK4 repressing cell cycle progression and cell growth in vitro and in vivo and induced the sensitivity of cells to DDP by regulating the c-Myc/CCND1/CDK4/E2F1 pathway in NPC. Finally, miR-15a was negatively weak correlated with the expression of CDK4 in NPC. Conclusions Our studies demonstrate that CDK4 and miR-15a comprise an abnormal automodulatory feedback loop stimulating the pathogenesis and inducing chemotherapy resistance in NPC.